Low-Grade Esthesioneuroblastoma Presenting as SIADH: A Review of Atypical Manifestations. (4th December 2012) - Senchak, Andrew; Freeman, Judy; Ruhl, Douglas; Senchak, Jordan; Klem, Christopher
Abstract : Esthesioneuroblastoma (ENB) is a neuroendocrine tumor that typically manifests as advanced stage malignancy in the superior nasal cavity. The hallmark symptoms include nasal obstruction and epistaxis, which result from local tissue invasion. Atypical clinical features can also arise and must be considered when diagnosing and treating ENB. These can include origin in an ectopic location, unusual presenting symptoms, and associated paraneoplastic syndromes. The case described here reports a nasal cavity ENB with atypical clinical features that occurred in a young female. Her tumor was low grade, appeared to arise primarily from the middle nasal cavity, and presented as syndrome of inappropriate antidiuretic hormone (SIADH). She also became pregnant shortly after diagnosis, which had implications on her surgical management. We review the atypical features that uncommonly occur with ENB and the clinical considerations that arise from these unusual characteristics.